Does â€œGoodâ€ Governance Promote Economic Growth According to Countries’ Conditional Income Distribution - Alshammari, Nayef; Alshuwaiee, Wael; Aleissa, NourElhuda (Journal of Reviews on Global Economics, 2019)
This study identifies the relative impact of â€œgoodâ€ governance on comparative economic growth performance for a large sample of countries classified based on their relative income distributions, namely; low income countries, middle income countries, and high income countries. The data set covers 100 countries throughout the period for 1996 to 2018. The empirical model is estimated with econometric pooled Ordinary Least Squares (OLS), random effects, fixed effects techniques and using the Hausman Test. According to the appropriate fixed effects estimated model, findings suggest that â€œgoodâ€ governance generally has a positive and statistically significant effect on economic growth across all countries in the sample. However, results confirm that the impact of â€œgoodâ€ governance differs according to conditional income distributions among countries. Indicators of â€œgoodâ€ governance for low income countries are more likely to affect economic growth than those for middle and high income countries. Specifically, findings show that the dominant governance indicators for economic growth in low income countries include government effectiveness, political stability, regulatory quality, rule of law, and voice and accountability. Findings also show that control of corruption seems not to influence economic growth for high and low income countries. There are some policy implications that can be drawn for countries to develop a variety of policies toward the role of governance in the economy according to their income distributions.